(3OeL GdeUGQas - (3CfWhGf(B, (3GdfGTas ((3WQGHdS(B:s (3GdeDSSI GdMOjKI ddcJGH(B,s, 2000)
(3GdGfOeGL CaVd GdNjGQGJ CeGe GdHfhc heDSSGJ GdeGd GdChQhHjI bHd WQM GdjhQh(B- (3GdEfOeGL GdeUQaj aj VhA GdYedI GdGQhHjI(B- (3JSGQY YedjGJ GdOeL hGdTQGA aj GdeUGQa GdGhQhHjI(B- (3GfOeGL eUGQa GdaQfSj(B- (3GdWGbI GdaGFVI hGdJcGdja GdJUGYOI(B- (3XGgQI GdEfOeGL(B- (3ahQI GdEfOeGLGJ JeJO Gdi Hfhc GjWGdjG(B- (3GdfbhO eGVjG hMGVQG heSJbHdGs
Keywords: (3GdShb GdeGdjIs; (3GdeUGQas